Hai visto i Canadesi?: A study of the Social Interactions between Canadian Soldiers and Italian Civilians before, during, and after the Battle of Ortona - Cavasin, Zachary David (University of Ottawa (Canada), 2010)
This thesis is the first study to examine Canadian and Italian interactions in Ortona from December 1943 until April 1944. The Canadian presence in Ortona is not remembered by the people of the town simply in the context of military operations. As the Canadians occupied Ortona and the surrounding areas for four months, interactions occurred within the context of combat operations, periods of relaxation, and throughout the process of rebuilding infrastructure and developing an economy. Canadian military historians have largely neglected to provide accounts of the various engagements between Canadian soldiers and Italian civilians before, during, and after the Battle of Ortona, unless they affected operations, intelligence, and civil control. The result of these civil-military relationships provided numerous benefits to Canadian and Italian alike. Italians provided Canadian soldiers with intelligence, shelter, food, and psychological support. In turn, the Canadians provided the Italians with medical assistance, food, financial support, and technical support in the rebuilding of Ortona. The interactions promoted Canadians as separate from the other Allied forces in the region and created unique friendships that defined the liberator and the liberated through their mutual dependencies. As historians have focused entirely on the unfolding of military operations in the region of Ortona, this thesis argues that the value of the interactions and the reconstruction process help explain why most Ortonesi developed a positive collective memory of Canadian soldiers.
Keywords: History, European.; History, Military.